Socialization of Gender Stereotypes Related to Attributes and Professions Among Young Spanish School-Aged Children - Solbes-Canales, Irene; Valverde-Montesino, Susana; Herranz-Hernández, Pablo (Frontiers in Psychology, 2020)
Modern societies increasingly show more egalitarian attitudes related to sexism and gender equality. However, there is still an important gender gap in wages and professions as well as in expectations surrounding male and female characteristics. Developmental studies carried out from an ecological perspective confirm that these influences come from the closest environments (mainly family and school) but also from more distant systems such as media or cultural values. As children are socialized in these norms and values, they increasingly internalize those schemes and use them to judge others, to choose friends and playmates, and to construct expectations of them. On this basis, the aim of this study was to examine the degree of gender bias internalization in a group of Spanish children. Two tasks were applied to a group of 149 public school boys and girls (aged 4 to 9 years). Results showed that, already from an early age, the participants had internalized traditional gender roles, especially when asked to assign masculine attributes. Moreover, group differences were found given that boys seemed to be more aware of expectations surrounding masculinity and girls assigned the attributes associated with femininity to women more often than boys. Furthermore, a developmental pattern similar to one obtained in previous studies was observed. Younger children already apply gender roles as part of their increasing acquisition of knowledge in the social field, but there is a big increase in the strength of this bias as they grow older. Psychological and educational implications of these findings are discussed, especially considering that the male gender role seems to be more rigid and less malleable. In this regard, developmental and environmental studies should be considered when designing early intervention programs to reduce sexism and to promote equity in schools and families. As research has already shown what type of environments affect children´s acquisition of traditional gender roles, society must make an effort to promote more egalitarian environments that will serve as protective factors in their future psychological, social and professional development.